PENGARUH PARTISIPASI PEMAKAI SISTEM INFORMASI, KEMAMPUAN TEKNIK PERSONAL, DAN PROGRAM PELATIHAN PADA KINERJA SISTEM INFORMASI AKUNTANSI (SIA) DI LEMBAGA PERKREDITAN DESA (LPD) KECAMATAN DENPASAR SELATAN - Ni Putu Rani Artha Mevia Dewi; Eka Putri Suryantari; Putu Aristya Adi Wasita (Journal of Applied Management and Accounting Science, 2024)
This study aims to determine the effect of information system user participation, personal technical skills, and training programs on accounting information system performance. The research method used in this research is quantitative research method with primary data obtained from questionnaire data measured on a Likert scale. This research was conducted at LPDs in South Denpasar District. The sampling method used was purposive sampling, namely the method of determining the sample based on the criteria set by the researcher with the number of samples taken as many as 68 respondents. Data analysis using multiple linear regression with data presentation assisted by SPSS version 24. Based on the results of the study, it is known that information system user participation has a positive effect on the performance of accounting information systems, personal technical abilities have a positive effect on the performance of accounting information systems and training programs have a positive effect on the performance of accounting information systems.